Peningkatan Kemampuan Cipta dan Baca Puisi melalui Metode Demonstrasi di MAN 2 Kota Cirebon - Atin Masyfu’ah (Jurnal Pendidikan Madrasah, 2023)
This study aims to determine the application of demonstration methods to Indonesian learning in improving the ability to create and read poetry. This research is an action research, conducted in two cycles including planning, implementation, observation, and reflection activities. The subject of the study was students of class XII IPS-2 MAN 2 Cirebon City consisting of 28 students. The results showed that the average score of learning outcomes in the first cycle was 73 with a learning completion of 71%. In cycle II, it obtained a score of 81 with a learning completion of 97%. The results of the observations of students and teachers showed a significant improvement. In cycle I, the performance of teachers and student activities is quite good, and in cycle II it is categorized as very good. The application of demonstration methods can improve students' ability to create and read poetry, it can also increase student participation and activity in learning. The demonstration method can be recommended to the teacher Indonesian to be applied in the learning process.